Preparation method and application of cobalt phosphide loaded noble metal nanosheet catalyst

Through polyvinylpyrrolidone-ascorbic acid aqueous reducing agent and microwave reaction methods, ultra-thin cobalt phosphide-supported precious metal nanosheet catalyst was prepared, which solved the problem of complex preparation process of existing CoP catalysts and easy material agglomeration, achieved efficient and stable electrocatalytic hydrogen production activity, and reduced costs.

CN119824456AActive Publication Date: 2025-04-15SHANDONG HAIHUA GRP CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510327895.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-15
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

The existing CoP catalyst preparation process is complex, involving the production of high temperatures and toxic gases, and the materials are prone to agglomeration, limiting their application in electrolytic water.

Method used

Using polyvinylpyrrolidone assisted, L-ascorbic acid aqueous solution reducing agent and microwave reaction, an ultra-thin cobalt phosphide-supported precious metal nanosheet catalyst was prepared, which avoided high-temperature heating and the generation of toxic gases, and maintained the morphological characteristics of the nanosheets.

Benefits of technology

The prepared catalyst has a high specific surface area and good conductivity, which significantly improves catalytic activity and stability, exhibits excellent electrocatalytic hydrogen production activity in the entire pH range, and reduces the load of precious metals and reduces the overall cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824456A_ABST
    Figure CN119824456A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a cobalt phosphide supported noble metal nanosheet catalyst, and belongs to the technical field of electrolyzed water catalysts.The preparation method comprises the following steps that divalent cobalt salt and polyvinylpyrrolidone are dissolved in deionized water, and a metal cobalt salt solution is obtained; dropwise adding an L-ascorbic acid aqueous solution to carry out reduction reaction to obtain a cobalt nano-sheet precursor; ultrasonically dispersing the cobalt nano-sheet precursor and a VIII main group noble metal salt in ethanol, and reacting to obtain a noble metal-loaded cobalt nano-sheet intermediate; and mixing and grinding the cobalt nano-sheet intermediate loaded with the noble metal and red phosphorus, and carrying out microwave reaction to obtain the cobalt phosphide loaded noble metal nano-sheet catalyst. The catalyst has an ultrathin nanosheet structure, the contact area of active sites and electrolyte is increased, and the catalyst shows excellent catalytic activity in the field of hydrogen production by electrolysis of water in a full pH range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water electrolysis catalysts, and specifically relates to a preparation method and application of a high-activity cobalt phosphide-loaded noble metal nanosheet catalyst. Background Art

[0002] The development of clean water electrolysis hydrogen production technology will be the key. The current mainstream water electrolysis hydrogen production technologies mainly include alkaline water electrolysis and proton exchange membrane water electrolysis in acidic environments. However, the two hydrogen production technologies in different pH environments are both limited by the kinetics of the hydrogen evolution reaction (HER), and catalysts are often used in industry to accelerate the reaction.

[0003] At present, precious metal catalysts are still recognized as the most effective and stable catalysts for water electrolysis, but the high cost hinders the possibility of large-scale industrial application. Cobalt phosphide (CoP), as a transition metal compound, is inexpensive and easy to adjust the electronic structure through atomic modification to enhance electrocatalytic activity. Therefore, using CoP as a carrier to modify precious metal atoms, utilizing metal-carrier interactions, adjusting the electronic structure between precious metal atoms and CoP carriers, and improving the intrinsic activity of precious metals are the keys to improving catalytic performance. However, there are still many defects in the preparation of CoP materials. The preparation process is complicated, contains toxic gases, and is easy to agglomerate during the preparation process, which restricts its application in water electrolysis.

[0004] The Chinese patent document with publication number CN118047369A discloses a method for preparing a cubic metal organic framework phosphide derivative material of cobalt phosphide-phosphorus doped carbon (CoP-PC) and its application. The cubic Co-MOF is used as a precursor and a one-step calcination method is used to prepare a metal organic framework phosphide derivative CoP-PC with a small particle size and a single shape.

[0005] The Chinese patent document with publication number CN104393312A discloses a method for preparing a highly active and highly stable Pt-CoP / C anode electrocatalyst with ultra-low platinum loading for direct methanol fuel cells. The carrier and cobalt chloride hexahydrate are dispersed in water and evaporated to obtain a first composite carrier; the first composite carrier is mixed with sodium hypophosphite hydrate for grinding and reacting for one hour, washed and dried to obtain a second composite carrier; the second composite carrier is dispersed in ethylene glycol, chloroplatinic acid is added, and ultrasonic dispersion and stirring are performed to obtain a first suspension; the first suspension is stirred at room temperature and the pH value is adjusted with sodium hydroxide to obtain a second suspension; the second suspension is subjected to microwave irradiation, washed and dried to obtain a supported Pt-CoP / C catalyst.

[0006] There are two main problems with the preparation methods of the above two CoP catalysts. First, in the process of preparing CoP catalysts, the synthesis steps are complicated, involving high temperature and other conditions, and flammable and toxic PH3 gas is produced; second, the atoms of the prepared CoP catalysts are easily agglomerated, which reduces the number of active sites, resulting in a low specific surface area of ​​the carrier, which is not conducive to the loading of precious metal atoms. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a cobalt phosphide-supported noble metal nanosheet catalyst, wherein the catalyst prepared by the method can efficiently electrocatalyze water hydrogen evolution in a full pH range.

[0008] In order to achieve the above object, the present invention adopts the following technical solution, which specifically includes the steps: (1) dissolving a divalent cobalt salt and polyvinyl pyrrolidone in deionized water to obtain a metal cobalt salt solution; adding an L-ascorbic acid aqueous solution dropwise to the metal cobalt salt solution until the solution completely turns black to obtain a suspension; centrifugally washing and drying the suspension to obtain a cobalt nanosheet precursor; (2) ultrasonically dispersing the cobalt nanosheet precursor in ethanol, then adding a noble metal salt of Group VIII, stirring to obtain a suspension, centrifuging and washing the suspension, and vacuum drying to obtain a cobalt nanosheet intermediate loaded with a noble metal; (3) The cobalt nanosheet intermediate loaded with precious metals and red phosphorus are mixed and ground, and subjected to microwave reaction under an inert atmosphere. After the reaction is completed, the reaction mixture is washed and dried with hot alkali solution and deionized water, respectively, to obtain a cobalt phosphide loaded with precious metal nanosheet catalyst.

[0009] Furthermore, in step (1), the divalent cobalt salt is one of cobalt nitrate, cobalt chloride or cobalt acetate; and the mass ratio of the cobalt salt to polyvinyl pyrrolidone in the divalent cobalt salt is 1:1-1.5.

[0010] Furthermore, in step (2), the noble metal salt of Group VIII contains Ru 3+ or Pt 4+ or Ir 3+ or Pd 2+ Any one of the metal salts; the mass ratio of the cobalt nanosheet precursor to the precious metal salt is 1:0.05~0.2; the stirring time is 12~24h.

[0011] Furthermore, in the step (3), the mass ratio of the cobalt nanosheet intermediate loaded with precious metal to red phosphorus is 1:1.5-2; the microwave power is 500-800w; and the microwave reaction time is 180-300s. The thickness of the prepared cobalt phosphide loaded with precious metal nanosheet catalyst is 5-20nm, and the equivalent diameter is 300-500nm.

[0012] The present invention also provides an application of the cobalt phosphide-loaded noble metal nanosheet catalyst prepared by the method in electrolyzing water to produce hydrogen in a full pH range.

[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The technical solution of the present invention successfully prepares a cobalt phosphide loaded precious metal nanosheet catalyst with an ultra-thin nanosheet structure by using polyvinyl pyrrolidone as an auxiliary, L-ascorbic acid aqueous solution as a reducing agent, and microwave reaction. The macromolecular chain structure of polyvinyl pyrrolidone has a steric effect, which enables the divalent cobalt salt to self-assemble into an ordered group and construct a sheet structure; the divalent cobalt salt is reduced to metallic cobalt by using L-ascorbic acid aqueous solution as a reducing agent. Compared with traditional reducing agents, L-ascorbic acid has moderate reducibility and mild reaction, which avoids the agglomeration of metallic cobalt nanosheets and maintains the morphological characteristics of the nanosheets to obtain a metallic cobalt nanosheet precursor; the cobalt nanosheet intermediate loaded with precious metals is mixed with red phosphorus and then reacted with microwave radiation to prepare a cobalt phosphide nanosheet catalyst loaded with precious metals. Compared with the traditional high-temperature heating method for phosphating, microwave radiation can achieve uniform heating of the sample, reduce the reaction temperature, shorten the reaction time, avoid the temperature gradient that may occur in the traditional high-temperature heating method for phosphating and the thermal agglomeration phenomenon of the cobalt phosphide nanosheet catalyst loaded with precious metals, and improve the catalytic activity and stability of the product.

[0014] (2) The technical solution of the present invention adopts a cobalt phosphide-loaded precious metal nanosheet catalyst prepared by using polyvinyl pyrrolidone as an auxiliary, L-ascorbic acid aqueous solution as a reducing agent, and microwave reaction, and has an ultra-thin nanosheet structure, the thickness of which is 5~20nm, and the equivalent diameter is 300~500nm; the ultra-thin structure gives it a very large specific surface area, increases the contact area between the active site and the electrolyte, and is conducive to fully loading and exposing the precious metal active sites, thereby significantly improving the rate and efficiency of the catalytic reaction; the ultra-thin structure also has good electrical conductivity, which is conducive to the rapid transfer of electrons and further improves the catalytic activity; by regulating the mass ratio of divalent cobalt salt to polyvinyl pyrrolidone, the thickness and size of the divalent cobalt sheet structure can be regulated, thereby changing the thickness and size of the catalyst, and the thickness and size of the catalyst affect the catalytic activity of the catalyst. When the mass ratio of divalent cobalt salt to polyvinyl pyrrolidone is 1:1~1.5, the catalyst has the most ideal catalytic activity.

[0015] (3) The microwave reaction used in the technical solution of the present invention for phosphating has a reaction time of only 180 to 300 seconds compared to traditional high-temperature phosphating, which greatly shortens the reaction time. At the same time, microwave radiation can avoid the production of toxic substances such as phosphine in traditional high-temperature phosphating, reducing pollution to the environment, and is more environmentally friendly and economical. In addition, the technical solution of the present invention greatly simplifies the reaction steps while controlling the mass ratio of the cobalt nanosheet intermediate loaded with precious metals and red phosphorus to 1:1.5 to 2, which greatly improves the reaction activity of the cobalt phosphide-loaded precious metal nanosheet catalyst.

[0016] (4) The high-activity cobalt phosphide-loaded precious metal nanosheet catalyst prepared by the technical solution of the present invention realizes electron transfer between the cobalt phosphide carrier and the precious metal by loading precious metal atoms on cobalt phosphide, optimizes the adsorption and desorption of the intermediates at the active sites, and thus accelerates the hydrogen evolution activity of the catalyst in the full pH range; and the precious metal is loaded on the ultra-thin cobalt phosphide nanosheet, which can achieve better dispersion of precious metal atoms and improve atomic utilization. Compared with traditional catalysts loaded with precious metals, on the basis of improving catalytic activity, the precious metal loading can be reduced, thereby reducing the overall cost of the catalyst.

[0017] (5) The technical solution of the present invention provides a highly active cobalt phosphide-loaded precious metal nanosheet catalyst suitable for the field of hydrogen production by electrolysis of water, which achieves 10 mA cm in alkaline, acidic, and neutral solutions of 1 M KOH aqueous solution, 0.5 M H2SO4 aqueous solution, and 1 M PBS neutral solution. -2 When the current density is , the overpotentials are 75-90 mV, 33-56 mV, and 102-126 mV, respectively. Therefore, the technical solution of the present invention can effectively evolve hydrogen in different acidic, alkaline, and neutral environments, and exhibits excellent electrocatalytic hydrogen production activity in the full pH range. The hydrogen evolution reaction in the full pH range can be applied to a variety of industrial processes, such as water electrolysis, hydrogen production, and wastewater treatment, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a transmission electron microscopy (TEM) image of the catalyst prepared in Example 1; Figure 2 is the X-ray powder diffraction pattern (XRD) of the catalyst prepared in Example 1; Figure 3 X-ray photoelectron spectroscopy (XPS) of the catalyst prepared in Example 1 and the catalyst prepared in Comparative Example 4; Figure 4 is a transmission electron microscopy (TEM) image of the catalyst prepared in Comparative Example 1; Figure 5 is a transmission electron microscopy (TEM) image of the catalyst prepared in Comparative Example 2; Figure 6 is a transmission electron microscopy (TEM) image of the catalyst prepared in Comparative Example 3; Figure 7 is a transmission electron microscopy (TEM) image of the catalyst prepared in Comparative Example 5; Figure 8 is an electrochemical linear sweep (LSV) curve diagram of the catalyst in Example 1; Fig. 9 This is the electrochemical current-time (It) curve of the catalyst in Example 1. DETAILED DESCRIPTION

[0019] The present invention is further described below by way of examples and drawings, but the protection scope of the present invention is not limited thereto. Example 1

[0020] (1) dissolving 0.177 g of cobalt chloride and 0.266 g of polyvinyl pyrrolidone in 100 mL of deionized water to obtain a metal cobalt salt solution; adding a 1 mol / L L-ascorbic acid aqueous solution dropwise to the metal cobalt salt solution until the solution completely turns black to obtain a suspension, which is then centrifuged, washed and dried to obtain a cobalt nanosheet precursor; (2) 0.1 g of the cobalt nanosheet precursor was ultrasonically dispersed in 20 mL of ethanol, and then 10 mg of ruthenium trichloride was added. After stirring for 12 h, a suspension was obtained. The suspension was centrifuged and washed, and vacuum dried at 60° C. to obtain a cobalt nanosheet intermediate loaded with a precious metal; (3) After 0.2 g of red phosphorus and 0.1 g of the cobalt nanosheet intermediate loaded with precious metals were fully mixed and ground, the mixture was placed in a microwave reactor in an argon atmosphere at a power of 700 W for 180 s. After the reaction, a 1 mol / L hot NaOH aqueous solution at 60 °C was used, stirred for 1 h, and then washed with water to finally obtain a cobalt phosphide nanosheet loaded with precious metal Ru catalyst, named 2D-Ru-CoP. Example 2

[0021] (1) dissolving 0.177 g of cobalt nitrate and 0.177 g of polyvinyl pyrrolidone in 100 mL of deionized water to obtain a metal cobalt salt solution; adding a 1 mol / L L-ascorbic acid aqueous solution dropwise to the metal cobalt salt solution until the solution completely turns black to obtain a suspension, which is then centrifuged, washed and dried to obtain a cobalt nanosheet precursor; (2) 0.1 g of the cobalt nanosheet precursor was ultrasonically dispersed in 20 mL of ethanol, and then 5 mg of ruthenium trichloride was added. After stirring for 24 h, a suspension was obtained. The suspension was centrifuged and washed, and vacuum dried at 60° C. to obtain an intermediate of cobalt nanosheets loaded with precious metals; 3) 0.15 g of red phosphorus and 0.1 g of the collected cobalt nanosheet intermediate loaded with precious metals were fully mixed and ground, and then placed in a microwave reactor in an argon atmosphere at a power of 700 w for 300 s. After the reaction, a 1 mol / L hot NaOH aqueous solution at 60°C was used, stirred for 1 h, and then washed with water to finally obtain a cobalt phosphide loaded precious metal Ru nanosheet catalyst. Example 3

[0022] (1) dissolving 0.177 g of cobalt acetate and 0.195 g of polyvinyl pyrrolidone in 100 mL of deionized water to obtain a metal cobalt salt solution; adding a 1 mol / L L-ascorbic acid aqueous solution dropwise to the cobalt metal salt solution until the solution completely turns black to obtain a suspension, which is then centrifuged, washed and dried to obtain a cobalt nanosheet precursor; (2) 0.1 g of cobalt nanosheet precursor was ultrasonically dispersed in 20 mL of ethanol, and then 15 mg of ruthenium trichloride was added. After stirring for 12 h, a suspension was obtained. The suspension was centrifuged and washed, and vacuum dried at 60° C. to obtain an intermediate cobalt nanosheet loaded with precious metals; (3) 0.2 g of red phosphorus and 0.1 g of the collected cobalt nanosheet intermediate loaded with precious metals were thoroughly mixed and ground, and then placed in a microwave reactor in an argon atmosphere at a power of 700 W for 180 s. After the reaction, a 1 mol / L hot NaOH aqueous solution at 60 ° C was used, stirred for 1 h, and then washed with water to finally obtain a cobalt phosphide loaded precious metal Ru nanosheet catalyst. Example 4

[0023] (1) dissolving 0.177 g of cobalt acetate and 0.212 g of polyvinyl pyrrolidone in 100 mL of deionized water to obtain a metal cobalt salt solution; adding a 1 mol / L L-ascorbic acid aqueous solution dropwise to the cobalt metal salt solution until the solution completely turns black to obtain a suspension, which is then centrifuged and washed and dried to obtain a cobalt nanosheet precursor; (2) 0.1 g of the cobalt nanosheet precursor was ultrasonically dispersed in 20 mL of ethanol, and then 20 mg of ruthenium trichloride was added. After stirring for 18 h, a suspension was obtained. The suspension was centrifuged and washed, and vacuum dried at 60° C. to obtain an intermediate of cobalt nanosheets loaded with precious metals; (3) 0.16 g of red phosphorus and 0.1 g of the collected cobalt nanosheet intermediate loaded with precious metals were thoroughly mixed and ground, and then placed in a microwave reactor in an argon atmosphere at a power of 700 W for 270 s. After the reaction, a 1 mol / L hot NaOH aqueous solution at 60 ° C was used, stirred for 1 h, and then washed with water to finally obtain a cobalt phosphide loaded precious metal Ru nanosheet catalyst. Example 5

[0024] (1) dissolving 0.177 g of cobalt acetate and 0.23 g of polyvinyl pyrrolidone in 100 mL of deionized water to obtain a metal cobalt salt solution; adding a 1 mol / L L-ascorbic acid aqueous solution dropwise to the cobalt metal salt solution until the solution completely turns black to obtain a suspension, which is then centrifuged, washed and dried to obtain a cobalt nanosheet precursor; (2) 0.1 g of cobalt nanosheet precursor was ultrasonically dispersed in 20 mL of ethanol, and then 10 mg of ruthenium trichloride was added. After stirring for 24 h, a suspension was obtained. The suspension was centrifuged and washed, and vacuum dried at 60° C. to obtain an intermediate cobalt nanosheet loaded with precious metals; (3) 0.17 g of red phosphorus and 0.1 g of the collected cobalt nanosheet intermediate loaded with precious metals were thoroughly mixed and ground, and then placed in a microwave reactor in an argon atmosphere at a power of 700 W for 240 s. After the reaction, a 1 mol / L hot NaOH aqueous solution at 60 ° C was used, stirred for 1 h, and then washed with water to finally obtain a cobalt phosphide loaded precious metal Ru nanosheet catalyst. Example 6

[0025] (1) dissolving 0.177 g of cobalt acetate and 0.248 g of polyvinyl pyrrolidone in 100 mL of deionized water to obtain a metal cobalt salt solution; adding a 1 mol / L L-ascorbic acid aqueous solution dropwise to the cobalt metal salt solution until the solution completely turns black to obtain a suspension, which is then centrifuged, washed and dried to obtain a cobalt nanosheet precursor; (2) 0.1 g of cobalt nanosheet precursor was ultrasonically dispersed in 20 mL of ethanol, and then 10 mg of chloroplatinic acid was added. After stirring for 12 h, a suspension was obtained. The suspension was centrifuged and washed, and vacuum dried at 60 ° C to obtain an intermediate of cobalt nanosheet loaded with precious metals; (3) 0.18 g of red phosphorus and 0.1 g of the collected cobalt nanosheet intermediate loaded with precious metals were thoroughly mixed and ground, and then placed in a microwave reactor in an argon atmosphere at a power of 700 W for 210 s. After the reaction, a 1 mol / L hot NaOH aqueous solution at 60 ° C was used, stirred for 1 h, and then washed with water to finally obtain a cobalt phosphide-loaded precious metal Pt nanosheet catalyst, named 2D-Pt-CoP. Example 7

[0026] (1) dissolving 0.177 g of cobalt acetate and 0.266 g of polyvinyl pyrrolidone in 100 mL of deionized water to obtain a metal cobalt salt solution; adding a 1 mol / L L-ascorbic acid aqueous solution dropwise to the cobalt metal salt solution until the solution completely turns black to obtain a suspension, which is then centrifuged, washed and dried to obtain a cobalt nanosheet precursor; (2) 0.1 g of cobalt nanosheet precursor was ultrasonically dispersed in 20 mL of ethanol, and then 10 mg of iridium trichloride was added. After stirring for 12 h, a suspension was obtained. The suspension was centrifuged and washed, and vacuum dried at 60° C. to obtain an intermediate cobalt nanosheet loaded with precious metals; (3) 0.19 g of red phosphorus and 0.1 g of the collected cobalt nanosheet intermediate loaded with precious metals were thoroughly mixed and ground, and then placed in a microwave reactor in an argon atmosphere at a power of 700 W for 180 s. After the reaction, a 1 mol / L hot NaOH aqueous solution at 60 ° C was used, stirred for 1 h, and then washed with water to finally obtain a cobalt phosphide-loaded precious metal Ir nanosheet catalyst, named 2D-Ir-CoP. Example 8

[0027] (1) dissolving 0.177 g of cobalt acetate and 0.266 g of polyvinyl pyrrolidone in 100 mL of deionized water to obtain a metal cobalt salt solution; adding a 1 mol / L L-ascorbic acid aqueous solution dropwise to the metal cobalt salt solution until the solution completely turns black to obtain a suspension, which is then centrifuged, washed and dried to obtain a cobalt nanosheet precursor; (2) 0.1 g of cobalt nanosheet precursor was ultrasonically dispersed in 20 mL of ethanol, and then 10 mg of noble metal palladium dichloride was added. After stirring for 12 h, a suspension was obtained. The suspension was centrifuged and washed, and vacuum dried at 60 ° C to obtain an intermediate of cobalt nanosheet loaded with noble metals; (3) 0.2 g of red phosphorus and 0.1 g of the collected cobalt nanosheet intermediate loaded with precious metals were thoroughly mixed and ground, and then placed in a microwave reactor in an argon atmosphere at a power of 700 W for 180 s. After the reaction, a 1 mol / L hot NaOH aqueous solution at 60 ° C was used, stirred for 1 h, and then washed with water to finally obtain a cobalt phosphide-loaded precious metal Pd nanosheet catalyst, named 2D-Pd-CoP. Example 9

[0028] (1) dissolving 0.177 g of cobalt acetate and 0.215 g of polyvinyl pyrrolidone in 100 mL of deionized water to obtain a metal cobalt salt solution; adding a 1 mol / L L-ascorbic acid aqueous solution dropwise to the metal cobalt salt solution until the solution completely turns black to obtain a suspension, which is then centrifuged and washed and dried to obtain a cobalt nanosheet precursor; (2) 0.1 g of cobalt nanosheet precursor was ultrasonically dispersed in 20 mL of ethanol, and then 10 mg of noble metal ruthenium trichloride was added. After stirring for 12 h, a suspension was obtained. The suspension was centrifuged and washed, and vacuum dried at 60 ° C to obtain an intermediate of cobalt nanosheet loaded with noble metal; (3) 0.2 g of red phosphorus and 0.1 g of the collected cobalt nanosheet intermediate loaded with precious metals were thoroughly mixed and ground, and then placed in a microwave reactor in an argon atmosphere at a power of 700 W for 180 s. After the reaction, a 1 mol / L hot NaOH aqueous solution at 60 ° C was used, stirred for 1 h, and then washed with water to finally obtain a cobalt phosphide loaded precious metal Ru nanosheet catalyst. Comparative Example 1

[0029] The difference between Comparative Example 1 and Example 1 is that polyvinyl pyrrolidone is not used in step 1, and the other steps remain unchanged. Comparative Example 2

[0030] The difference between Comparative Example 2 and Experimental Example 1 is that in step 1, the ratio of divalent cobalt salt to polyvinyl pyrrolidone is changed to 1:2, and the other steps remain unchanged. Comparative Example 3

[0031] The difference between Comparative Example 3 and Experimental Example 1 is that sodium borohydride is used as a reducing agent in step 1, and the other steps remain unchanged. Comparative Example 4

[0032] The difference between Comparative Example 4 and Experimental Example 1 is that there is no noble metal Ru modification (ie, there is no step 2), and the other steps remain unchanged. Comparative Example 5

[0033] The difference between Comparative Example 5 and Experimental Example 1 is that microwaves are not used in step 3, and the remaining steps remain unchanged. The specific implementation scheme is as follows: 0.2g of sodium hypophosphite and 0.1g of the precious metal loaded cobalt nanosheet intermediate collected in step 2 are placed in the upstream and downstream of a tubular furnace in an argon atmosphere, respectively, heated to 350°C, and reacted for 2h to obtain a precious metal Ru modified CoP catalyst. Comparative Example 6

[0034] The difference between Comparative Example 6 and Experimental Example 1 is that the ratio of the precursor obtained in step 2 to red phosphorus is changed to 1:1, and the other steps remain unchanged. Comparative Example 7

[0035] The difference between Comparative Example 7 and Experimental Example 1 is that in step 3, the microwave reaction time of the precursor and red phosphorus is changed to 120 s, and the other steps remain unchanged. Test Example 1

[0036] The 2D-Ru-CoP prepared in Example 1 was subjected to TEM test, and the results were as follows: Figure 1As shown, the prepared cobalt phosphide supported precious metal nanosheet catalyst has an ultra-thin nanosheet structure, the thickness of the nanosheet is 5-20nm, and the equivalent diameter is 300-500nm; the 2D-Ru-CoP prepared in Example 1 was tested by XRD, and the results are as follows Figure 2 As shown; in Comparative Example 1, polyvinyl pyrrolidone was not used, and the prepared Ru-CoP was subjected to TEM test, and the results were as follows Figure 4 As shown; in Comparative Example 2, the ratio of metal cobalt salt to polyvinyl pyrrolidone was changed to 1:2, and the prepared catalyst was subjected to TEM test. The results are as follows Figure 5 As shown; in Comparative Example 3, sodium borohydride was used as a reducing agent, and the prepared catalyst was subjected to TEM testing, and the results were as follows Figure 6 As shown; in Comparative Example 5, microwave reaction was not used, and the prepared catalyst was subjected to TEM test, and the results were as follows Figure 7 shown.

[0037] Figure 1 The results show that polyvinyl pyrrolidone is used in Example 1 of the present technical solution to prepare a highly active cobalt phosphide-loaded precious metal nanosheet catalyst (2D-Ru-CoP) with an ultra-thin nanosheet structure. The steric hindrance effect of the macromolecular chain structure of polyvinyl pyrrolidone and its self-assembled ordered collective are used to avoid the agglomeration of nanoparticles during the preparation process. By controlling the mass ratio of cobalt salt to polyvinyl pyrrolidone to 1:1~1.5, the prepared catalyst has an ultra-thin nanosheet structure, and the thickness of the nanosheet is about 5-20nm and the diameter is 300-500nm. Figure 2 : is the XRD pattern of the 2D-Ru-CoP catalyst prepared in Example 1. The results show that the 2D-Ru-CoP catalyst corresponds to the standard card CoP (PDF#29-0497), proving the successful implementation of microwave phosphating and the feasibility of this technical solution.

[0038] The catalyst prepared in Comparative Example 1, because no polyvinyl pyrrolidone was used, was composed of stacked nanoparticles ( Figure 4 As shown), it is difficult to load precious metal atoms.

[0039] In Comparative Example 2, the ratio of polyvinyl pyrrolidone to metal cobalt salt was changed, and the prepared catalyst consisted of a portion of nanosheets, and its thickness was significantly greater than that of the 2D-Ru-CoP catalyst prepared in Example 1.

[0040] In Comparative Example 3, sodium borohydride was used as the reducing agent. However, due to its strong reducing property, the reaction was fast, and the results were as follows: Figure 6 As shown, the prepared catalyst has the phenomenon of nanoparticle agglomeration and it is impossible to obtain an ultrathin nanosheet structure.

[0041] The catalyst prepared in Comparative Example 5 ( Figure 7The 2D-Ru-CoP catalyst prepared in Example 1 (as shown) is composed of large nanoparticles, which are significantly larger than the 2D-Ru-CoP catalyst prepared in Example 1, and has no obvious nanosheet structure. This indicates that microwave radiation can achieve uniform heating of the sample, avoiding the temperature gradient and thermal agglomeration that may occur in traditional high-temperature heating methods, thereby improving the uniformity of the nanomorphology of the catalyst.

[0042] Therefore, the catalyst prepared by the present technical solution has an ultra-thin structure, which gives it a very large specific surface area, increases the contact area between the active sites and the electrolyte, and is conducive to fully exposing the active sites of the precious metals, thereby significantly improving the rate and efficiency of the catalytic reaction. Test Example 2

[0043] The XPS test results of the catalysts prepared in Example 1 and Comparative Example 4 are as follows: Figure 3 Shown Figure 3 The Co2p high-resolution spectra of the 2D-Ru-CoP catalysts prepared in Example 1 and Comparative Example 4 are shown in Table 1. The characteristic peak with a binding energy of 778.3 eV in the 2D-Ru-CoP catalyst prepared in Example 1 of the present technical solution corresponds to Co2p 3 / 2 The Co-P in the 2D-CoP catalyst prepared in Comparative Example 4 has a binding energy of 778.1 eV. This electronic structure has obvious differences, indicating that there is a metal-metal interaction between the CoP catalyst and Ru. Therefore, by taking advantage of the fact that CoP is easy to adjust and improve properties through atomic modification strategies, the loading of the noble metal atom M on CoP is successfully achieved, optimizing the adsorption and desorption of the intermediates on the active sites, thereby accelerating the HER activity of the catalyst in the full pH range. Application Example 1

[0044] The materials prepared in Examples 1-9 and the catalyst materials prepared in Comparative Examples 1-7 were applied to hydrogen evolution reaction in a full pH range, including the following application steps: (1) Electrode preparation The electrode is 10 uL of 5 mg mL -1 The catalyst slurry (5 mg sample ultrasonically dispersed in 0.95 mL isopropanol and 0.05 mL Nafion solution) was coated on a glassy carbon electrode (electrode area: 0.07065 cm 2 ) as the working electrode, the reference electrode and the counter electrode were reversible hydrogen electrode and stone rod electrode respectively; the stability electrode was coated with 150uL of catalyst slurry on an area of ​​1cm 2 The carbon cloth was placed on the electrode and tested after natural drying.

[0045] (2) Catalytic activity test The electrochemical activity evaluation method is to use Chenhua CHI 760E electrochemical workstation to test the hydrogen evolution performance of catalyst materials in different medium solutions under a three-electrode system. The preparation methods and concentrations of alkaline, acidic and neutral electrolyte solutions are 1M KOH aqueous solution, 0.5M H2SO4 aqueous solution and 1M PBS neutral solution, respectively. The corresponding pH values ​​measured by pH meter are approximately 14, 0 and 7. The electrochemical performance evaluation is carried out by linear sweep voltammetry (LSV) in the voltage region of -0.5 V-0 V (vs. RHE) with a scan rate of 5 mV S -1 All LSV polarization curves were obtained with iR (95 %) compensation; the current-time curve (It) was used at 10 mA cm -2 The stability of the catalyst was evaluated at a current density of .

[0046] Figure 8 The LSV curves of the 2D-Ru-CoP catalyst prepared in Example 1 in 1M KOH aqueous solution, 0.5M H2SO4 aqueous solution, and 1M PBS neutral solution are shown. The results show that in 1M KOH, the prepared 2D-Ru-CoP catalyst only needs an overpotential of 80 mV to achieve 10 mA cm -2 In the acidic 0.5 M H2SO4 aqueous solution, the prepared 2D-Ru-CoP catalyst only needs 42 mV overpotential to achieve the same current density. In the more environmentally friendly neutral 1 M PBS solution, the catalyst also shows excellent catalytic activity, achieving 10 mA cm -2 At a current density of , the overpotential is only 110 mV.

[0047] The electrochemical activity test was also carried out on Example 2-9. The results are shown in Table 1. The prepared ultra-thin cobalt phosphide nanosheets have a good carrier effect.

[0048] Compared with Example 1, the Ru-CoP catalyst prepared without adding polyvinyl pyrrolidone in Comparative Example 1 achieved 10 mA cm -2 At a current density of , the overpotentials are 171, 101, and 242 mV, respectively, which are much lower than 80, 42, and 110 mV in Example 1.

[0049] Compared with Example 1, when the content of metal cobalt salt and polyvinyl pyrrolidone was changed to 1:2 in Comparative Example 2, its overpotentials in alkaline, acidic and neutral environments were 130, 108 and 201 mV, respectively, which were much lower than 80, 42 and 110 mV in Example 1.

[0050] Compared with Example 1, the reducing agent was changed in Comparative Example 3, and sodium borohydride was used as the reducing agent. Its overpotentials in alkaline, acidic and neutral environments were 162, 120 and 221 mV, respectively, which were much lower than 80, 42 and 110 mV in Example 1. This indicates that by designing an ultra-thin nanosheet structure with a high specific surface area, the structural environment around the active site in the CoP catalyst is improved, the contact area between the active site and the electrolyte is increased, and the material diffusion rate is improved.

[0051] Compared with Example 1, the 2D-CoP catalyst without precious metal Ru prepared in Comparative Example 4 achieved 10 mA cm -2 When the current density is , the overpotentials are 182, 132, and 237 mV, respectively, which are much lower than those in Example 1. This shows that loading precious metal atoms can enhance the adsorption capacity of reactants and increase the concentration of reactants on the catalyst surface, thereby accelerating the reaction rate and realizing the application of the prepared catalyst in the full pH range.

[0052] Compared with Example 1, the catalyst prepared by microwave reaction in Comparative Example 5 has overpotentials of 142, 102, and 179 mV in alkaline, acidic, and neutral environments, respectively, which are much lower than 80, 42, and 110 mV in Example 1. Therefore, the catalyst prepared by microwave reaction in the technical solution achieves uniform heating of the sample, avoids the temperature gradient and agglomeration phenomenon that may occur in the traditional phosphating high-temperature heating method, and never improves the catalytic activity.

[0053] Compared with Example 1, in Comparative Example 6, the mass ratio of microwave reaction precursor to red phosphorus was changed, and the overpotentials of the prepared catalyst in alkaline, acidic and neutral environments were 144, 101 and 162 mV, respectively, which were much lower than 80, 42 and 110 mV in Example 1.

[0054] Compared with Example 1, in Comparative Example 7, the overpotentials of the catalyst prepared by changing the microwave reaction time in alkaline, acidic and neutral environments were 204, 158 and 271 mV, respectively, which were much lower than those in Example 1.

[0055]

Claims

1. A method for preparing a cobalt phosphide-supported noble metal nanosheet catalyst, characterized in that: The following steps are involved: (1) dissolving a divalent cobalt salt and polyvinyl pyrrolidone in deionized water to obtain a metal cobalt salt solution; adding an L-ascorbic acid aqueous solution dropwise to the metal cobalt salt solution until the solution completely turns black to obtain a suspension; centrifugally washing and drying the suspension to obtain a cobalt nanosheet precursor; (2) ultrasonically dispersing the cobalt nanosheet precursor in ethanol, then adding a noble metal salt of Group VIII, stirring to obtain a suspension, centrifuging and washing the suspension, and vacuum drying to obtain a cobalt nanosheet intermediate loaded with a noble metal; (3) The cobalt nanosheet intermediate loaded with precious metals and red phosphorus are mixed and ground, and subjected to microwave reaction under an inert atmosphere. After the reaction is completed, the reaction mixture is washed and dried with hot alkaline solution and deionized water, respectively, to obtain a highly active cobalt phosphide loaded with precious metal nanosheet catalyst.

2. The method for preparing the cobalt phosphide-supported noble metal nanosheet catalyst according to claim 1, characterized in that: In the step (1), the divalent cobalt salt is one of cobalt nitrate, cobalt chloride or cobalt acetate; and the mass ratio of the divalent cobalt salt to polyvinyl pyrrolidone is 1:1-1.

5.

3. The method for preparing the cobalt phosphide-supported noble metal nanosheet catalyst according to claim 1, characterized in that: In the step (2), the noble metal salt of Group VIII is Ru 3+ or Pt 4+ or Ir 3+ or Pd 2+ Any one of the metal salts; the mass ratio of the cobalt nanosheet precursor to the noble metal salt of the VIII main group is 1:0.05~0.2; the stirring time is 12~24h.

4. The method for preparing the cobalt phosphide-supported noble metal nanosheet catalyst according to claim 1, characterized in that: In the step (3), the mass ratio of the cobalt nanosheet intermediate loaded with precious metal to red phosphorus is 1:1.5-2; the microwave power is 500-800 W; and the microwave reaction time is 180-300 s.

5. The method for preparing the cobalt phosphide-supported noble metal nanosheet catalyst according to any one of claims 1 to 4, characterized in that: The thickness of the prepared cobalt phosphide-loaded noble metal nanosheet catalyst is 5-20 nm, and the equivalent diameter is 300-500 nm.

6. An application of a cobalt phosphide-supported noble metal nanosheet catalyst prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The cobalt phosphide-supported noble metal nanosheet catalyst is used for electrolysis of water to produce hydrogen in a full pH range.

Citation Information

Patent Citations

  • Preparation method of ultralow platinum-loading capacity Pt-CoP / C anode electrocatalyst for high-activity high-stability direct methanol fuel cell

    CN104393312A

  • Preparation method and application of cobalt phosphide-phosphorus doped carbon cubic nano electrode material

    CN118047369A

  • Composite hydrogen evolution electrocatalytic material as well as preparation method and application thereof

    CN109046408A

  • Carbon-supported nickel oxide modified platinum rhodium nanorod electrocatalyst for alkaline hydrogen evolution reaction and preparation method and application thereof

    CN111085219A

  • Carbon-supported platinum-cobalt-rhodium nanorod catalyst for acidic hydrogen evolution reaction, and preparation method and application thereof

    CN111111690A